Digital Technology and the Economic Transformation of Nigeria via the lens of Delta State: Opportunities, Challenges, and Future Prospects - Jammy Seigha Guanah; Paul Bebenimibo (Britain International for Academic Research (BIAR) Publisher, 2025)
Digital technology is rapidly transforming the global economy, and Nigeria, as Africa's largest economy, has not been left out of this trend. The objectives of this paper were to ascertain if the media can contribute to the economic transformation of Nigeria through digital technology; identify critical areas that need to be addressed to promote the growth of Nigeria's digital economy, and determine if digital technology can contribute to economic development in Nigeria. A quantitative method was used to explore the experiences and perceptions of media practitioners and industry experts regarding the role of media in driving digital transformation in Nigeria. Questionnaire was utilised as the instrument for data collection. This study was based on the Uses and Gratifications Theory. Findings from the study revealed that the media can play crucial role in the economic transformation of Nigeria through digital technology. It was also found that some challenges that Nigeria faces in harnessing the full potential of digital technology include inadequate infrastructure, limited digital skills, and insufficient regulatory frameworks. Also, it was established that digital technology can contribute to economic development in Nigeria. The paper concluded that digital technology has the potential to significantly transform Nigeria's economy, creating new business opportunities, enhancing access to markets, and increasing productivity. It was recommended that the media should do more in strengthening collaboration and partnerships between government, industry, academia, and civil society organisations to drive digital transformation and contribute to the economic transformation of Nigeria. Furthermore, government should expand access to reliable Internet connectivity across Nigeria, including remote and underdeveloped areas; upgrade technological infrastructure to support digital innovation and entrepreneurship, and foster public-private partnerships to accelerate the development of digital infrastructure